Victory on Two Fronts : The Cleveland Indians and Baseball through the World War II Era - Longert, Scott (Book collections on Project MUSE., 2022)
"Like other teams, the Cleveland Indians suffered as World War II drained rosters and distracted fans. But in 1945, star pitcher Bob Feller returned from naval service and was soon joined by the American League's first Black players: Larry Doby and Satchel Paige. This book shows how, in 1948, they led the Indians to a World Series championship"--